Everything you want to know about Business Continuity - Drewitt, Tony (IT Governance Publishing, 2012)
The book will guide you through domestic and international standards relating to business continuity, with particular reference to ISO22301. Companies achieving certification under the Standard will communicate to their stakeholders their commitment to uninterrupted supply.
Keywords: Crisis management.; Emergency management.; Business planning.; Information technology -- Management.; elektronické knihy; electronic books